Adding Energy Storage Materials to Improve the Productivity of Solar Distillation - Attia Mohammed El Hadi; Bellila Abdelkader; Benoudina Belkheir (University Of Eloued جامعة الوادي, 2020)
The southeast region of Algeria suffers from a great socio-economic problem that affects a large population. Faced with the unavailability of drinking water, solar distillation; which appears to be a suitable and inexpensive solution; was adopted by local researchers. Improving the productivity of a solar greenhouse distiller is the subject of several researches in the world. The idea is to add energy storage materials to a single-slope solar distillation. The search for materials is more effective. This technique has a major impact on the productivity of solar distillation.
Intervention
Keywords: Solar distillation; Energy; Solar Still; Freshwater; Energy Storage Materials